ANALISIS HUKUM AURAT PRIA - Agus Syihabudin (Jurnal Sosioteknologi, 2011)
Humans have a civilization (civilization) that distinguishes it from animal creatures. With this civilization, humans appear to be caliph (leader) on earth. One of the human civilization is the dress code. Dressed according to Islamic teaching ethics does not simply include appropriate and inappropriate, but set a mandatory closed genitalia from view of others and relate to legal requirements worship prayers. The study of male genitalia are closely related to the objective conditions of Indonesian society that tends to get dressed without closing the thigh as when exercising. In fact, most people in West Irian until today there are those who wear koteka, ie clothing that simply closes the groin and anus. Conceivably, if the thigh assessed male genitalia, then males wearing shorts forbidden by the legal status of "unlawful", the consequence of sin if it broke. Similarly, Papuans wearing koteka prayer, worship considered void or invalid. Limit male genitalia in the discourse of Islamic jurisprudence was controversial. Some scholars regard the thigh as the genitalia. Others claim that the thigh does not include genitalia. Differences of opinion of the fuqaha is rooted in several traditions are considered contrary to each other. Accordingly, analyzing the truth of the traditions it was deemed important to determine the actual boundaries of the male genitalia to be a good guideline when prayers and worship in the order of everyday dress. The results of restriction analysis of male genitalia may also be an ethical consideration for the players in the industry, especially apparel, art and design and development of information technology and others.